Ketofast cookbook : recipes for intermitent fasting and timed ketogenic meals from a world-class doctor and an internationally renowned chef - Mercola, Joseph; Evans, Pete, 1973- (Hay House, Inc., 2019)
Natural-health expert Dr. Joseph Mercola and top Australian chef Pete Evans share a firm belief that food can be medicine--that what we eat offers us powerful tools to reshape our health. In their second co-authored cookbook, they explore the science behind intermittent fasting and the practice of timing ketogenic meals for maximum health benefits--a unique combination of principles they call KetoFasting. Drawing on Dr. Mercola's expertise and visionary work in natural medicine, and Pete Evans's experience as an award-winning restaurateur, cookbook author, and TV chef, this book offers: *Insight into the history and cultural relevance of fasting *Guidance for a healthy ketogenic lifestyle *Strategies to boost your body's detox processes--including a detailed guide to using sauna therapy for detoxing *Healthy supplements to support KetoFasting *Delicious recipes for soups, broths, snacks, and more --all illustrated with mouthwatering full-color photographs shot in Pete Evans's own studio.